Effect of arbuscular mycorrhizal fungi on the potential of three wild plant species for phytoextraction of mercury from small-scale gold mine tailings - Fiqri, A; Utomo, W H; Handayanto, E (Brawijaya University, 2016)
A study that was aimed to explore the effects of arbuscular mycorrhizal (AM) fungi inoculation on the potential of wild plant species (Paspalum conjugatum, Cyperus kyllingia, and Lindernia crustacea) for phytoextraction of mercury from small-scale gold mine tailings was conducted in a glasshouse. Each of the plant seedlings was planted in a plastic pot containing 10 kg of planting medium (mixture of tailings and compost; 50%: 50% by weight). Treatments tested were three plant species and doses of AM fungi inoculation, i.e. 0 and 30 spores/plant. At harvest of 63 days, plant shoot and root were analyzed for mercury concentration. The remaining planting media in the pots were used for growing maize for 84 days. The results showed that the most potential plant species for phytoextraction of mercury was Paspalum conjugatum, while the most mercury tolerant plant was Cyperus kyllingia. Without AM fungi inoculation, the highest accumulation of mercury (44.87 mg/kg) was found in the root of Paspalum conjugatum. If AM fungi were inoculated, the highest accumulation of mercury (56.30 mg/kg) was also found in the shoot of Paspalum conjugatum. Results of the second experiment proved that the growth and biomass production of maize after mycophytoextraction by the plant species were higher than those of maize grown on media without mycophytoextraction of mercury.